Aberdeen-Angus cattle - Gilkison, Charles A. (My University, 1906)
Introduction: Little is known of the early history of any of our domestic animals. They all belong to Lthe class Mammalia , order Ruminatia, family Bovidae , genus Bos and all except the zebus or humped cattle to the sub-genus Taurus. They are most likely a cross between the genii Bos Urus and Bos Longifrons, which inhabited the British Isles and northern Europe prior to the dawn of the Christian era. The former was a very fierce animal, nearly as large as an elephant but otherwise much resembling the cattle of later times. The Bos Longifrons was smaller than most of our breeds of cattle today, and not as nearly like them in general conformation as the Urus. The constantly changing surroundings to which they were subject until well along in the seventeenth century, when we have our first meager description of any cattle, would make quite a change in their appearance. As far back as there is any account there have been polled cattle in Scotland, but probably they were once horned and originated from some "sport". Of the four breeds of cattle native to the British Isles, only one, the Ayrshire, had any foreign blood introduced. The two polled breeds, Galloway, and Aberdeen-Angus, are nearer related to each other than to the others. The Galloways are ranker, and coarser in hair, thicker and stiffer in skin, and slower maturing than the Angus. The differences between them and between the West Highlands was due chiefly to climatic conditions, care and food. The Aberdeen-Angus cattle are indigenous to the counties of Aberdeen, Forfar (which contains most of the district formerly called Angus) and the surrounding country in the north-east part of Scotland. Here they reign supreme to the present day. The time of the formation of the breed is unknown, but was before the latter part of the seventeenth century.
Citation: Gilkison, Charles A. Aberdeen-Angus cattle. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Animal Husbandry; Aberdeen Cattle; Angus Cattle; Theses